Environment-modulated crystallization of Cu2O and CuO nanowires by electrospinning and their charge storage properties - Harilal, Midhun; Krishnan, Syam G.; Pal, Bhupender; Reddy, M. Venkatashamy; Mohd Hasbi, Ab. Rahim; M. M., Yusoff; Rajan, Jose (American Chemical Society, 2018)
This article reports the synthesis of cuprous oxide (Cu2O) and cupric oxide (CuO) nanowires by controlling the calcination environment of electrospun polymeric nanowires and their charge storage properties. The Cu2O nanowires showed higher surface area (86 m2 g−1) and pore size than the CuO nanowires (36 m2 g−1). Electrochemical analysis was carried out in 6 M KOH, and both the electrodes showed battery-type charge storage mechanism. The electrospun Cu2O electrodes delivered high discharge capacity (126 mA h g −1) than CuO (72 mA h g −1) at a current density of 2.4 mA cm −2. Electrochemical impedance spectroscopy measurements show almost similar charge-transfer resistance in Cu2O (1.2 Ω) and CuO (1.6 Ω); however, Cu2O showed an order of magnitude higher ion diffusion. The difference in charge storage between these electrodes is attributed to the difference in surface properties and charge kinetics at the electrode. The electrode also shows superior cyclic stability (98%) and Coulombic efficiency (98%) after 5000 cycles. Therefore, these materials could be acceptable choices as a battery-type or pseudocapacitive electrode in asymmetric supercapacitors.